2023
DOI: 10.1177/13684302221147004
|View full text |Cite
|
Sign up to set email alerts
|

Threatened by the immoral, challenged by the incompetent: Cardiovascular responses to intragroup morality vs. competence evaluations

Abstract: In group contexts, moral judgments are used as social influence tactics to regulate the behavior of group members. We argue that communicating moral disapproval with the aim of adapting group members’ behavior might backfire because it elicits (negative) threat rather than (positive) challenge. In two experiments, we examined the motivational consequences of negative morality (vs. competence) evaluations in group contexts. Participants worked on a group task while cardiovascular indices of challenge and threat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 60 publications
0
2
0
Order By: Relevance
“…Here, participants were asked to verbally reflect on the role of morality in solving (management) dilemmas, after recalling their own past moral failures. Results showed that the recollection of past moral shortcomings was associated with a psychophysiological threat response-indicative of the appraisal that situational demands exceed one's coping abilities (Van der Lee et al, 2023) Taken together, these research findings thus reveal that being called out for one's past moral wrongdoings makes people feel guilty, raises a psychophysiological threat response that is generally maladaptive, and reduces people's sense of being able to address the situation or to motivate them to improve their behavior in the future (Van der Lee et al, 2016Lee et al, , 2023.…”
Section: Unraveling the Vicious Cyclementioning
confidence: 99%
“…Here, participants were asked to verbally reflect on the role of morality in solving (management) dilemmas, after recalling their own past moral failures. Results showed that the recollection of past moral shortcomings was associated with a psychophysiological threat response-indicative of the appraisal that situational demands exceed one's coping abilities (Van der Lee et al, 2023) Taken together, these research findings thus reveal that being called out for one's past moral wrongdoings makes people feel guilty, raises a psychophysiological threat response that is generally maladaptive, and reduces people's sense of being able to address the situation or to motivate them to improve their behavior in the future (Van der Lee et al, 2016Lee et al, , 2023.…”
Section: Unraveling the Vicious Cyclementioning
confidence: 99%
“…For instance, the work attitudes (satisfaction, commitment) of employees in different job types and professions primarily relate to the perceived morality of their organization (Ellemers et al., 2011). In general, people are reluctant to affiliate with individuals lacking in morality, as they see this as a threat to the positive identity of the group (Brambilla et al., 2013), and suffer cardiovascular threat as a result (Van der Lee et al., 2023). Experimental research accordingly reveals that people are more likely to exclude individuals with inferior morals from their work team, and are less willing to help a new colleague lacking in morals than lacking in competence (Pagliaro et al., 2013; Van der Lee et al., 2017).…”
Section: Framework and Description Of Relevant Theory And Researchmentioning
confidence: 99%